The “formative research” in mutidisciplinary studies on architectural and urban heritage - Almonacid, Rodrigo; Fernández-Maroto, Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Given the devaluation of university education due to the split between teaching and research, “formative research” is proposed as a formula for meaningful learning. An epistemological framework is offered based on the complexity of knowledge in the Humanities, and a methodological approach organised on the basis of a multidisciplinary and converging approach. Results of its application in the study of problems related to architectural and urban heritage are presented. Several case studies are shown that demonstrate its flexibility, its interactivity in learning and its potential to transcend from the university community to the general public.